Pattern of pediatric dermatoses in Northeast India - Karthick Nagarajan; Nandakishore Singh Thokchom; Khaidem Ibochouba; Kapila Verma; N A Bishurul Hafi (Wolters Kluwer Medknow Publications, 2017)
Background: The prevalence of pediatric skin diseases varies worldwide. Pediatric dermatoses require a separate view from adult dermatoses as there are important differences in clinical presentation, treatment, and prognosis. Aims and Objectives: To study the clinical and etiological presentation of dermatoses in the pediatric population in Northeast India. Materials and Methods: The study was carried out at a tertiary care center in Northeast region for 18 months (from December 2012 to May 2014). Cases under the age of 12 years were selected based on purposive sampling method. Results: Infections (36.25%) were the most common cause of skin diseases in the study group comprising 400 patients. Eczematous diseases (14.5%), pigmentary disorders (14.25%), and infestations (13.25%) were the other common causes. Varicella (6%), impetigo contagiosum (5%), and candidiasis (4.5%) were the most common viral, bacterial, and fungal diseases, respectively. Scabies (12.25%) was the most common individual disease in the present study. The prevalence of hand, foot, and mouth disease was high constituting 4% of the study group. Dyshidrotic eczema (6.5%), pityriasis alba (7.5%), and vitiligo (3.5%) were also common. Miliarial dermatitis and polymorphic light eruption also contributed significantly (5.25%) reflecting the typical pattern of the tropical skin diseases. Atopic dermatitis, genetic disorders, and nutritional deficiency disorders had a very low prevalence. Conclusion: The study finding that the majority of the diseases could be grouped into fewer than 8 disease categories may help in more accurate diagnosis. Significant proportions of the dermatoses are infections followed by eczematous and pigmentary diseases. Age, sex, locality, the income of the parents, family history, and season of presentation have an influential role in the pattern of distribution of the pediatric skin diseases.